Management of Sickle Cell Disease: A Review for Physician Education in Nigeria (Sub-Saharan Africa) - Ademola Samson Adewoyin (Anemia)
Sickle cell disease (SCD) predominates in sub-Saharan Africa, East Mediterranean areas, Middle East, and India. Nigeria, being the most populous black nation in the world, bears its greatest burden in sub-Saharan Africa. The last few decades have witnessed remarkable scientific progress in the understanding of the complex pathophysiology of the disease. Improved clinical insights have heralded development and establishment of disease modifying interventions such as chronic blood transfusions, hydroxyurea therapy, and haemopoietic stem cell transplantation. Coupled with parallel improvements in general supportive, symptomatic, and preventive measures, current evidence reveals remarkable appreciation in quality of life among affected individuals in developed nations. Currently, in Nigeria and other West African states, treatment and control of SCD are largely suboptimal. Improved knowledge regarding SCD phenotypes and its comprehensive care among Nigerian physicians will enhance quality of care for affected persons. This paper therefore provides a review on the aetiopathogenesis, clinical manifestations, and management of SCD in Nigeria, with a focus on its local patterns and peculiarities. Established treatment guidelines as appropriate in the Nigerian setting are proffered, as well as recommendations for improving care of affected persons.